Sensory Stimulation Improves Neurobehavioral Development in Preterm Infants - Rahmatika Alimuddin; Allendekania Allendekania; Reni Yustina; Mega Hasanul Huda (FORIKES, 2026)
Prematurity disrupts critical intrauterine sensory experiences and increases the risk of long‑term neurobehavioral developmental impairments in infants, particularly those receiving care in the Neonatal Intensive Care Unit (NICU). Sensory stimulation interventions offer a non‑pharmacological approach to support central nervous system maturation in preterm infants. This systematic review aimed to evaluate the effects of sensory stimulation on neurobehavioral development in preterm infants. Literature searches were conducted using the Population–Intervention–Comparison–Outcome (PICO) framework across PubMed, ProQuest, and ScienceDirect, focusing on randomized controlled trials published between 2015 and 2025. The review followed the Preferred Reporting Items for Systematic Reviews and Meta‑Analyses (PRISMA) guidelines, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Seven studies met the inclusion criteria. All reported significant improvements in neurobehavioral outcomes measured using the Neonatal Neurobehavioral Examination Scale (NNES), Neonatal Intensive Care Unit Network Neurobehavioral Scale (NNNS), Munich Neuromotor Development Examination (MNNE), Neonatal Behavioral Assessment Scale (NBAS), Dubowitz Neurological Examination, Alberta Infant Behavioral Scale (ABSS), and Infant Behavior Questionnaire‑Revised (IBQ‑R). Additional benefits included improved suck coordination, increased weight gain, enhanced physiological stability, and reduced length of hospital stay. In conclusion, sensory stimulation, particularly multisensory approaches effectively enhances neurobehavioral development in preterm infants and is recommended for integration into NICU care and early family‑centered intervention programs.Keywords: preterm infants; Neonatal Intensive Care Unit; neurobehavioral development; sensory stimulation